Impact of IT investment on financial performance in Saudi banks - Khadidja khaldi; Abrar Khaled Alnasser; Jawaher Mohammad Abdullah (Journal of North African Economies, 2025)
The research aims to analyze the impact of investment in Technology information on financial performance, and the investment in information technology consists of three components: investing in the number of ATMs, investing in software and technological systems, investing in technological banking devices, By applying to a sample of banks listed on the Saudi Market, the data were collected from the annual reports and published by these banks and statistics of the Central Bank of Saudi Arabia during the period 2016-2020, and based on time series data, and adopted a study mainly on the use of Program (E-views), the research found an impact of investment in Technology information on financial performance, where there is a weak inverse relationship between both software investment and technology systems with return on assets, , and there is a strong correlation between both investment in ATMs and return on assets…